Education and Efficient Redistribution - Robert A. J. Dur; Coenraad N. Teulings (Center for Economic Studies and ifo Institute (CESifo), 2001)
Should education be subsidized for the purpose of redistribution? The usual argument against subsidies to education above the primary level is that the rich take up most education, so a subsidy would increase inequality. We show that there is a counteracting effect: an increase in the stock of human capital reduces the return to human capital and, therefore, pre-tax income inequality decreases. We consider a Walrasian world with perfect capital and insurance markets. Hence, in the absence of a strive for redistribution, the market generates the efficient level of investment in human capital. When there is a demand for redistribution, the general equilibrium effects on relative wages might make a subsidy to education an ingredient of a second-best optimal redistribution policy. Stimulating human capital formation results in a compression of the wage distribution, and hence reduces the need for distortionary redistributive taxation. We also study the political viability of education subsidies.
Keywords: 330